An Analysis of the Financial Performance of PT Sekar Laut Tbk (SKLT) from 2021 to 2025 Based on Liquidity, Solvency, and Profitability Ratios - Bella Sripuspita; Alisya Putri Salsabil; Cindi Apriany; Nabila Khaerunnisa; Herayati Herayati (The Future of Education Journal, 2026)
This study aims to analyze the financial performance of PT Sekar Laut Tbk (SKLT) over a five-year period from 2021 to 2025. The analysis was conducted using the company's consolidated financial statements, including the consolidated statements of financial position and comprehensive income statements, with a focus on three categories of financial ratios: liquidity, solvency, and profitability ratios. The study employed a descriptive quantitative approach based on audited financial statements published by the company through the Indonesia Stock Exchange (IDX) and the company's official website. The findings indicate that PT Sekar Laut Tbk achieved consistent revenue growth, increasing from IDR 1.36 trillion in 2021 to IDR 2.65 trillion in 2025, representing a 95.2% increase over the five-year period. Net profit also increased significantly, rising from IDR 85 billion in 2021 to IDR 126 billion in 2025. Total assets more than doubled, growing from IDR 889 billion to IDR 1.80 trillion. The liquidity ratios generally indicated a healthy financial position, remaining above 1.5 times despite some fluctuations. The solvency ratios reflected a capital structure predominantly financed by equity, with the Debt-to-Equity Ratio (DER) remaining below 1.0 in most years. Profitability remained stable, with the Return on Equity (ROE) ranging from 9.5% to 15.7% throughout the study period.